2003
DOI: 10.1210/jc.2003-031174
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin in Human Cord Blood: Relation to Fetal Birth Weight and Gender

Abstract: Adiponectin is an adipocyte-derived plasma protein with insulin-sensitizing and antiatherosclerotic properties. The aim of this study was to examine whether adiponectin is present in human fetal blood, to define its association with fetal birth weight, and to evaluate whether dynamic changes in adiponectin levels occur during the early neonatal period. Cord blood adiponectin levels were extremely high (71.0 +/- 21.0 microg/ml; n = 51) compared with serum levels in children and adults and positively correlated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
103
5
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(136 citation statements)
references
References 49 publications
22
103
5
6
Order By: Relevance
“…This was in contrast to others, i.e. Sivan et al[ 17] and Kajantie et al [28], who analysed cord blood adiponectin in a large cohort of term newborns and found that it was correlated with neonatal BW. Although we could demonstrate an increase in adiponectin with advancing gestational age we found an independent positive association with BW.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This was in contrast to others, i.e. Sivan et al[ 17] and Kajantie et al [28], who analysed cord blood adiponectin in a large cohort of term newborns and found that it was correlated with neonatal BW. Although we could demonstrate an increase in adiponectin with advancing gestational age we found an independent positive association with BW.…”
Section: Discussioncontrasting
confidence: 99%
“…The lack of such negative feedback could contribute to the high adiponectin level in newborns. In addition it has been hypothesized that some particular features of the adipose tissue in newborns, including the presence of brown adipose tissue, might be responsible for the high levels of adiponectin in the fetal circulation [17]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High concentrations of circulating adiponectin have positive health effects such as reduction in proinflammatory cytokines [7], improvement in insulin sensitivity [8], and an increase in fatty acid metabolism [9]. Recently, several investigators reported much higher plasma adiponectin concentrations in cord blood than in the infants’ mothers [10,11,12,13] or in nonobese adults aged 23–50 years [14]. Adiponectin in cord blood is not derived from maternal or placental tissues [12] and does not seem to be related to maternal concentrations [13, 15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several investigators reported much higher plasma adiponectin concentrations in cord blood than in the infants’ mothers [10,11,12,13] or in nonobese adults aged 23–50 years [14]. Adiponectin in cord blood is not derived from maternal or placental tissues [12] and does not seem to be related to maternal concentrations [13, 15]. Some of these reports [12,13,14,15] and others [16, 17] showed a positive relationship between plasma adiponectin concentrations and birth weight; however, such relationships were not found in other studies [10, 11].…”
Section: Introductionmentioning
confidence: 99%